Atmospheric Plasma Spraying (APS) and Alloying as Methods to Modify Properties of the SSS Surface Layers - Barbara Lisiecka; Agata Dudek; Robert Ulewicz (Communications - Scientific letters of the University of Zilina, 2020)
Use of the powder metallurgy (PM) in production of various components has been growing in the automotive industry, including production of sintered stainless steels (SSSs). This study aims to improve the functional properties of SSSs by formation of the Cr3C2-NiCr coating by APS method. The next stage involved alloying of the surface of SSSs using the gas tungsten arc welding (GTAW). Analysis of microstructures was carried out using microscopy (metallographic microscope and scanning electron microscope). Furthermore, the study presents XRD (X-ray powder diffraction) examinations, mechanical properties and surface roughness measurements. The presented modification improved properties of the surface layers examined in the study and enabled a reduction in the wall thickness of the detail, which is important factor in the automotive and transport industry.